Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fnins.2019.00738
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Regional Cerebral Blood Flow, Functional Activity and Connectivity in Alzheimer’s Disease: A Combined ASL Perfusion and Resting State fMRI Study

Abstract: Recent studies have demonstrated a close relationship between regional cerebral blood flow (rCBF) and resting state functional connectivity changes in normal healthy people. However, little is known about the parameter changes in the most vulnerable regions in Alzheimer’s disease (AD). Forty AD patients and 30 healthy controls participated in this study. The data of resting-state perfusion and functional magnetic resonance imaging (fMRI) was collected. By using voxel-wise arterial spin labeling (ASL) perfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 66 publications
1
71
0
Order By: Relevance
“…ECN plays an important role in the integration of sensory and memory information, the regulation of cognition and behavior, and the working memory process with the prefrontal lobe as its core (Petersen et al, 2019). A combined arterial spin labeling (ASL), perfusion, and rsfMRI study confirms that the brain regions in AD where cerebral blood flow and ALFF decrease predict a disruption in the ECN (Zheng et al, 2019). However, the lack of consistent results for specific alterations in ECN fail to provide specific imaging markers in predicting the transition from MCI to AD.…”
Section: Introductionmentioning
confidence: 87%
“…ECN plays an important role in the integration of sensory and memory information, the regulation of cognition and behavior, and the working memory process with the prefrontal lobe as its core (Petersen et al, 2019). A combined arterial spin labeling (ASL), perfusion, and rsfMRI study confirms that the brain regions in AD where cerebral blood flow and ALFF decrease predict a disruption in the ECN (Zheng et al, 2019). However, the lack of consistent results for specific alterations in ECN fail to provide specific imaging markers in predicting the transition from MCI to AD.…”
Section: Introductionmentioning
confidence: 87%
“…Fourth, in this study, ALFF was employed to estimate the spontaneous activity changes induced by SD and rTMS. The ALFF approach showed higher sensitivity and specificity in detecting spontaneous brain activity and distinguishes some diseases from the normal control than the other fMRI indices [60,61]. However, network analysis including functional connectivity and effective functional connectivity analysis could better reflect the path of modulation of rTMS on working memory.…”
Section: Limitationsmentioning
confidence: 99%
“…Jandackova et al (2016) showed a marked decline in HRV in middle-aged individuals which seems to be secondary to other pathological conditions. Cognitive dementia is the result of multiple age-related neuropathies (Power et al, 2018) associated with cardiovascular risk factors (Oishi et al, 2017), such as chronic brain hypoperfusion (Zheng et al, 2019), which particularly affects the frontal cortex (Sherwood et al, 2011).…”
Section: Introductionmentioning
confidence: 99%